Difference In Shot’s Attributes Between Winning And Losing Teams In The 2018 Fifa World Cup - Hadji , Abderrahmen (sports creativity, 2025)
The aim of this study is to investigate the relationship between shot attributes and match outcome (Winning vs losing) in the 2018 FIFA World cup. Shot’s attributes are: Pattern of play, Origin, Outcome, Player (shooter) and coordinate of shots. 1313 shots from 105 unbalance game by team were studied. Data was provided by StatsBomb company. The results showed that, comparing to losing teams, winning teams use more shots from set pieces (P<0.05; ES=0.25), shoot more often from a counter attack (P<0.05; ES=0.22), and from regular play (P<0.05; ES=0.28), have more successful shots (P<0.001; ES=0.42), more ratio of success(P<0.01; ES=0.38), tend to involve more their attacking-midfield(P=0.087; ES=0.18), and forward (P=0.86; ES=0.2) at shooting, and their successful shots are mostly concentrated closer to target (P=0.06; ES=0.3), and relatively centered (P<0.05; ES=0.32). Coaches can use these findings to enhance their own players' performance.